Compressed air illness, or, so-called Caisson disease - Snell, E. Hugh (H.K. Lewis, 1896)
Following the construction of Blackwall Tunnel in London, many workers suffered from compressed air sickness. This book follows from the investigations and observations of the medical officer appointed by the London City Council.